Development of a windowless multi-wire proportional chamber (MWPC) counting system for measuring extended-area beta source. (August 2017) - Hwang, S.H.; Lee, J.M.; Lee, K.B.; Park, T.S.
Abstract: A windowless MWPC counting system has been developed to measure surface emission rate of extended-area sources. A new anode and guard plane design gives better electric-field uniformity in the (250×200) mm 2 sensitive volume relative to a previous-generation MWPC at KRISS, which has been used as a national standard with uncertainty < 1 % . The conditions of stable operation for the new MWPC system were studied, and the uncertainty was estimated with an extended-area 36 Cl source. The relative combined standard uncertainty was evaluated to be 0.23%, a 50% improvement over the previous-generation MWPC counting system. Highlights: New MWPC system has been developed at KRISS. The relative combined standard uncertainty is found to be 0.23% with the extended-area 36 Cl source (50% improvement).